2013
DOI: 10.1021/ic400340y
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Mediated Crystal-to-Crystal Interconversion between Discrete Lanthanide Complexes and One-Dimensional Coordination Polymers and Selective Sensing for Small Molecules

Abstract: Two isostructural 1D coordination polymers {[Ln(OAc)2(H2O)(OBPT)]·3H2O}n (HOBPT = 4,6-bis(2-pyridyl)-1,3,5-triazin-2-ol, Ln = Eu(3+), 1; Tb(3+), 3) and two discrete complexes [Ln(OAc)2(DMF)2(OBPT)] (Ln = Eu(3+), 2; Tb(3+), 4) have been synthesized in H2O-MeOH or DMF solvents, respectively. Their structures were identified by powder X-ray diffraction. Single-crystal X-ray studies for complexes 1 and 2 revealed that the coordination geometries of the Eu(3+) ions are similar and can be described as a distorted tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…[183-186,215a] In presence of ZnCl 2 , the BPT ligand undergone hydrolysis as indicated by the formation of [Zn(pz) 2 Cl 2 ] complex. [186] The same research group reported the Cu(II)mediated hydrolysis of the BPT ligand [215b] followed by complexation giving the followed by complexation Giri et al [134] [Ru(dmdptz)(phen)Cl](ClO Wu et al [136] [ Safin et al [143] [Cd( Frost et al [147] [Cd 2 (TpymT)( Safin et al [148] [Pb 2 (TPymT)(NO Wang et al [176] [ Soliman et al [185] [Cd(BPT) Carranza et al [169] [Ag(bdpdt) Berdiell et al [182] [ [Cu(TPTZ) 2 ](PF 6 ) 2 Breast cancer (MCF-7) Abdi et al [51] [Cu(TPTZ)(Ph 3 P) 2 ](PF 6 ) Cosensitized solar cells Báez-Castro et al [52,53] (Continues)…”
Section: Tpymt Ligandmentioning
confidence: 99%
See 2 more Smart Citations
“…[183-186,215a] In presence of ZnCl 2 , the BPT ligand undergone hydrolysis as indicated by the formation of [Zn(pz) 2 Cl 2 ] complex. [186] The same research group reported the Cu(II)mediated hydrolysis of the BPT ligand [215b] followed by complexation giving the followed by complexation Giri et al [134] [Ru(dmdptz)(phen)Cl](ClO Wu et al [136] [ Safin et al [143] [Cd( Frost et al [147] [Cd 2 (TpymT)( Safin et al [148] [Pb 2 (TPymT)(NO Wang et al [176] [ Soliman et al [185] [Cd(BPT) Carranza et al [169] [Ag(bdpdt) Berdiell et al [182] [ [Cu(TPTZ) 2 ](PF 6 ) 2 Breast cancer (MCF-7) Abdi et al [51] [Cu(TPTZ)(Ph 3 P) 2 ](PF 6 ) Cosensitized solar cells Báez-Castro et al [52,53] (Continues)…”
Section: Tpymt Ligandmentioning
confidence: 99%
“…Design and modification of the dipyridyl-based s-triazine ligands as a rigid multidentate ligands by insertion of a hydroxyl group, sulfhydryl, or amino group at the third carbon of the s-triazine core were explored by the research group of Cao and Ye in 2013. [136] This modification on the ligand structure offered numerous coordination sites due to the six potential binding sites exist in 4,6-bis(2-pyridyl)-striazin-2-ol (HOBPT; 185) as an example. Subsequently, they synthesized two 1D Ln(III) coordination polymers including Eu(III) and Tb(III) with HOBPT ligand.…”
Section: 4-bis(2-pyridyl)-6-aryl-s-triazine and Its Analogousmentioning
confidence: 99%
See 1 more Smart Citation
“…The versatility and tailorability of physicochemical properties of lanthanide ions make them key to an extremely wide range of techniques and devices (Jones, 2011;Pyykkö, 2015;Samson et al, 2011;Maurin et al, 2017;Guillou et al, 2016). During the past two decades, the design and synthesis of lanthanide coordination polymers (LnCPs) have received great attention due to their powerful attributes, originating from specific functional applications, such as photocatalysis (Qiao & Schelter, 2018), gas storage and separation (Banerjee et al, 2015;Roy et al, 2014;Alezi et al, 2015), magnetism (Liu et al, 2014;Zhang et al, 2015;Mohapatra et al, 2013;Cai et al, 2013;Zou et al, 2010), sensing (Wu et al, 2019(Wu et al, , 2013Chen et al, 2010;Dou et al, 2014;Chen et al, 2017;Zhou et al, 2018;Xu et al, 2017) and tunable luminescence (Cui et al, 2014;SeethaLekshmi et al, 2017;Bü nzli & Piguet, 2005;Xiao et al, 2016;Wu et al, 2011aWu et al, , 2017). These applications are made possible by the characteristic luminescent behaviour of ISSN 2052-5206 # 2019 International Union of Crystallography lanthanide elements, which stem from the shielding of their 4f core-like electrons and the large numbers of unpaired electrons of each Ln 3+ metal centre (Bü nzli & Piguet, 2005;Heffern et al, 2014;Woodruff et al, 2013;.…”
Section: Introductionmentioning
confidence: 99%
“…Such crystal-crystal transformations have been recently reported. 49 The molecular structure of compound 3 is given in Scheme 1 and in the SI. The molecular structure of compound 3 contains one gadolinium center in the asymmetric unit.…”
Section: Introductionmentioning
confidence: 99%